Comparative Analysis of Political Dynamics and Public Policy in Infrastructure Development: A Study of Indonesia and India - Napitupulu, Chindy Apriani; Dompak, Timbul; Salsabila, Lubna (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
Public infrastructure development is a critical component of a nation's economic progress. Indonesia and India, both with significant population sizes and complex infrastructure challenges, adopt distinct strategies in their public infrastructure development programs. This study aims to provide a comparative analysis of the political dynamics and public policies shaping infrastructure development in Indonesia and India. By examining the disparities in policy approaches, implementation strategies, and the resulting effects on economic and social progress, this study offers insights into the effectiveness of different administrative practices. Employing a qualitative methodology, the research scrutinizes various public infrastructure development policies and relevant literature from both countries. Data collection involved documentation studies and comparative analysis. The findings reveal significant variations in development tactics, the involvement of public and private sectors, and the degree of community participation. Additionally, the study identifies the influence of government involvement, legislative frameworks, and financial resources on policy implementation and outcomes. Despite facing similar challenges in public infrastructure development, Indonesia and India's divergent policy approaches have led to different results. The study highlights the need for cross-country knowledge exchange to enhance policy efficiency and accelerate infrastructure development. Such advancements are essential for fostering economic growth and improving social well-being in both nations.